Investigating Urban Ergonomics Features through Healthy City Approach: The Case of Istanbul and Singapore - Turkyilmaz, Cigdem Canbay; Villani, Caterina (Environment-Behaviour Proceedings Journal, 2021)
This study aims to investigate urban ergonomics features through the healthy city approach. Analytic Hierarchy Process (AHP) is adopted to make a pairwise comparison and ranking of multiple features of urban ergonomics. A small online panel was organized with ten experts of architecture and urban design with a minimum of 10 years of experience. Findings from the literature were shared with these experts, and they were asked to compare the ergonomics features pairwise and rank them. For the next step, two main urban squares from Istanbul and two main public spaces of Singapore are examined. Keywords: Ergonomics; Healthy city; Istanbul; Singapore. eISSN: 2398-4287Â© 2021. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians), and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v6i16.2725